SK2 channel deletion reduces susceptibility to bupivacaine-induced cardiotoxicity in mouse. (October 2021) - Chen, H; Jin, Z; Fu, Z; Xia, F
Bupivacaine is frequently used for regional anesthesia and postoperative analgesia. However, an inadvertent intravenous injection can cause severe cardiotoxicity, manifesting as arrhythmia, hypotension, and even cardiac asystole. The mechanism of bupivacaine-mediated cardiotoxicity remains unclear. SK2 knockout mice (SK) and wild-type mice (WT) were divided into four groups, with 12 mice per group. We determined the difference in bupivacaine cardiotoxicity between SK2 knockout and WT mice by measuring the time to the first arrhythmia (Tarrhythmia ) and the time to asystole (Tasystole ). Secondary indicators of cardiotoxicity were the time from the beginning of bupivacaine infusion to 20% prolongation of the QT interval (TQT ) and the time to 20% widening of the QRS complex (TQRS ). Tarrhythmia and Tasystole were significantly longer in the SK-bupi group than in the WT-bupi group (both P < 0.05). TQT and TQRS were longer in the SK-bupi group than in the WT-bupi group (all P < 0.05). The time to 25%, 50%, and 75% reduction in HR in the SK-bupi group was significantly longer than in the WT-bupi group (all P < 0.05). Knocking out the SK2 channel can reduce bupivacaine-induced cardiotoxicity in the mouse.